Styl indywidualny w perspektywie genologii lingwistycznej - Witosz, Bożena (Stylistyka, 2021)
The author of the article analyses the relations between the category of genre and the one of style on three different planes: • lndividual style - functional style (language variety) • lndividual style - genre style (pattern) • Individual style - specific text The above mentioned contexts allow to present the issues connected with the study of the individual style, which could inspire the contemporary genology.